Fashion Futuring in the Anthropocene: Sustainable Fashion as "Taming" and "Rewilding". (2nd January 2019) - Payne, Alice
Abstract: The Anthropocene describes our current geological era, in which human activity has grown to become a planetary force. Interest in "sustainable fashion" reflects the necessity to address the social and environmental ills of fashion. Yet thinking on sustainable fashion remains chiefly industry and user-focused, examining narrow questions regarding how industry may shift practices, or how users may engage with fashion differently—hence only tacitly positioned within the context of the Anthropocene. Synthesizing scholarly and industry perspectives, this article establishes two positions on sustainable fashion, and aligns these with the philosophical positions of humanity's future in the Anthropocene, adopting ethicist Clive Hamilton's nomenclature. First, fashion's Prometheans, the techno-optimists, propose a future in which cleaner technologies can lead to the gradual evolution of a better industry. In contrast, fashion's Soterians take a cautionary approach, and seek to unbind fashion from the unsustainable growth imperative of capitalism itself. Under these two, the definition of "sustainable fashion" may differ, but, critically, their dialogue will shape the direction of fashion. Together, their actions create a "fashion futuring, " a dynamic process of negotiation between what I term the "taming" and the "rewilding" of fashion, within a world of our own making.